1981
DOI: 10.2135/cropsci1981.0011183x002100060038x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Defoliating Pests on Soybean Canopy CO2 Exchange and Reproductive Growth1

Abstract: Defoliation during reproductive growth of soybean [Glycine max (L.) Merr.] may significantly reduce yields. The objective of this study was to elucidate the relationships among organism‐induced defoliation, CO2 exchange rates, and reproductive growth in fieldgrown soybean. Soybean (‘Bragg’) plots were sprayed a factorial design with diflubenzuron (0.035 kg a.i./ha) and a benomyl‐maneb mixture (1.12 a.i./ha) on two dates, first at early flowering (5 August) and again at early pod set (19 August). Diflubenzuron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 0 publications
2
34
0
4
Order By: Relevance
“…Isto resulta em menor fonte de fotoassimilados, limitando o desenvolvimento das estruturas reprodutivas (demanda). Conforme relatado por INGRAM et al (1981), o efeito do desfolhamento sobre o rendimento de grãos demonstrou ter sido causado pela redução da interceptação da luz (IL) e fotossíntese do dossel. Outro fator que pode ter contribuído para a queda do rendimento foi a insuficiência de reservas que as plantas possuíam nos caules, ramos e pecíolos, para suprir a demanda das estruturas reprodutivas, mesmo permanecendo parte da área foliar como aconteceu no nível de 67% de desfolhamento.…”
Section: Resultsunclassified
“…Isto resulta em menor fonte de fotoassimilados, limitando o desenvolvimento das estruturas reprodutivas (demanda). Conforme relatado por INGRAM et al (1981), o efeito do desfolhamento sobre o rendimento de grãos demonstrou ter sido causado pela redução da interceptação da luz (IL) e fotossíntese do dossel. Outro fator que pode ter contribuído para a queda do rendimento foi a insuficiência de reservas que as plantas possuíam nos caules, ramos e pecíolos, para suprir a demanda das estruturas reprodutivas, mesmo permanecendo parte da área foliar como aconteceu no nível de 67% de desfolhamento.…”
Section: Resultsunclassified
“…Responses of this kind have been observed in grasses, Oesterheld (1992) showing that allocation towards the restoration of basic allometric ratios was a major priority regardless of the intensity of defoliation, Herbivory caused a significant decrease in SLA, Impacts of herbivory on SLA have not been covered to any degree in the literature. Both increases and decreases in response to insect feeding have been reported, but only two studies have examined the efTect of defoliators and there was no consensus (Bassman & Dickmann, 1982;Schmid et al, 1988), A decrease in SLA might occur as a result of selective feeding (Ingram et al, 1981), Gastrophysa preferentially eat the area of the leaf between the ribs, and this might cause a decrease in SLA, This does not, however, preclude the possibility that physiological responses to herbivory might also affect SLA. In an examination of the responses of Solidago altissima to herbivory caused by insects from three different feeding guilds, Meyer (1993) found that both xylem-feeding spittlebugs and leaf-chewing beetles reduced SLA, but the greater efTect was caused by the spittlebug which unlike the beetle did not cause a direct loss of leaf area.…”
Section: Discussionmentioning
confidence: 99%
“…É possível que a ocorrência tardia da doença e o baixo potencial de inóculo tenham contribuído para tal fato. Ingram et al (1981) relatam que o efeito da desfolha sobre a peso de grãos é causado pela redução da interceptação da luz e da fotossíntese. A tolerância da soja á desfolha é dependente de vários fatores como o nível de desfolha, o estádio fenológico na época da desfolha e fatores ambientais (PEDIGO; HUTCHINS; HIGLEY, 1986;PARCIANELLO et al, 2004).…”
Section: Fonte: Elaboração Dos Autoresunclassified